Depression mediates the relationship between alexithymia and obesity in the Northern Finland Birth Cohort 1966 (NFBC1966) - Ramzi, NH; Auvinen, J; Veijola, J; Miettunen, J; Ala-Mursula, L; Sebert, S; Keinänen-Kiukaanniemi, S; Svento, R; Jokelainen, J; Drenos, F; Dovey, TM; Järvelin, M-R; et al. (Journal of Affective Disorders, 2023)
Data availability: NFBC data is available from the University of Oulu, Infrastructure for Population Studies. Permission to use the data can be applied for research purposes via electronic material request portal. In the use of data, we follow the EU general data protection regulation (679/2016) and Finnish Data Protection Act. The use of personal data is based on cohort participant's written informed consent at his/her latest follow-up study, which may cause limitations to its use. Please contact NFBC project center (NFBCprojectcenter@oulu.fi) and visit the cohort website for more information. Background: The fact that a complex relationship exists between alexithymia and body mass index (BMI) is well established, but the underlying mechanisms remain poorly understood. Here, we explore the relationship between alexithymia and depressive symptoms in relation to adiposity measures, including the direct and indirect effect of alexithymia and depressive symptoms on obesity over a 15-year time-period, in the Northern Finland Birth Cohort 1966 (NFBC1966). Methods: The study included individuals from the Northern Finland Birth Cohort 1966 (NFBC1966) who had available data for adiposity measures (body mass index and waist-to-hip ratio), alexithymia (measured by the 20-Item Toronto Alexithymia Scale: TAS-20), depressive symptoms (measured by the 13-item depression subscale of Hopkins Symptom Checklist: HSCL-13) at age of 31 years (n = 4773) and 46 years (n = 4431). Pearson's (r) correlation, and multiple linear regression were used to investigate the relationships between alexithymia, depressive symptoms, and adiposity measures. The potential mediating role of depressive symptoms was examined via Hayes' procedure (PROCESS). Results: Positive correlations were confirmed between adiposity measures (BMI and WHR) and the TAS-20 score (and its subscale), but not between obesity and HSCL-13 score. The strongest correlation was between the DIF (difficulty identifying feelings) subscale of the TAS-20 and HSCL-13 at both time ...